Characteristics and health risk assessment of polycyclic aromatic hydrocarbons associated with dust in household evaporative coolers. (January 2020) - Nazmara, Shahrokh; Sorooshian, Armin; Delikhoon, Mahdieh; Baghani, Abbas Norouzian; Ashournejad, Qadir; Barkhordari, Abdullah; Basmehchi, Niloufar; Kasraee, Mahboobeh
Abstract: This study reports a characterization of indoor polycyclic aromatic hydrocarbons (PAHs) associated with dust (dust-PAHs) in household evaporative coolers and their associated health effects. Extensive analysis showed that the indoor dust-PAHs stemmed mostly from pyrogenic sources (vehicular emissions) with mean total concentrations limited between 131 and 429 ng g −1 . The distribution pattern of PAHs based on number of rings exhibited the following order of decreasing relative abundance: 4 > 3 > 5 > 6 > 2 rings. Results indicate that the mutagenicity of dust-PAHs exceeded their carcinogenicity, but that the potential carcinogenic effects are still significant. The mean lifetime cancer risk for different age groups for three pathways based on Model 2 (dermal (1.39 × 10 −1 to 1.91 × 10 −2 ), ingestion (2.13 × 10 −3 to 8.08 × 10 −3 ) and inhalation (1.62 × 10 −7 to 4.06 × 10 −7 )) was 7.4–146 times higher than values predicted by Model 1 (dermal (5.13 × 10 −5 to 3.03 × 10 −3 ), ingestion (9.34 × 10 −5 to 1.31 × 10 −3 ) and inhalation (7.13 × 10 −20 to 1.68 × 10 −20 )). Hence, exposure to dust-PAHs in household evaporative coolers lead to high risk, especially for children (less than 11 years) (HQ = 2.71 × 10 −20 to 54.8 and LTCRs = 7.13 × 10 −20 to 1.39 × 10 −1 ). Strategies should be considered to eliminate such pollutants to protect people, especially children, from the non-carcinogenic and carcinogenic effects by changing household evaporative coolers with other cooling systems. Graphical abstract: Image 1 Highlights: Dust-PAHs were measured in 9 household evaporative coolers in Tehran, Iran. The major source of dust-PAHs was traffic emissions. LMW-PAHs/HMW-PAHs ratio ranged from 0.38 to 0.69. HQ for dust-PAHs in different age groups exceeded the acceptable limit. LTCR for dust-PAHs in different age groups ranged from 1.45 × 10 −4 to 1.43 × 10 −1 . Abstract : This work is novel in that there are no reports to our knowledge of the nature and impacts of dust-PAHs for indoor environments associated with evaporative coolers as a transportation conduit between ambient air and living spaces. The results of this work have broad implications for other regions owing to the pervasiveness of evaporative coolers and dust.